Comparison of efficacy of chemical peeling with 25% trichloroacetic acid and 0.1% retinoic acid for facial rejuvenation - Yildirim, Selda; Gurel, Mehmet Salih; Gungor, Sule; Tekeli, Omur; Canat, Dilek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Skin aging is a problem which negatively affects the psyche of the person, social relations, as well as work life and health and which compels the patients to find appropriate treatment methods. Numerous treatment methods have been developed in order to delay aging and to reduce the aging effects in addition to having a younger, healthier and more beautiful facial appearance. Aim : To compare the efficiency, cosmetic results and possible adverse effects of the peeling treatment with 25% trichloroacetic acid (TCA) and 0.1% retinoic acid for facial rejuvenation in patients presenting with skin aging. Material and methods: Fifty female patients in total presenting with medium and advanced degree skin aging were subject to this study. Two separate treatment groups were formed; the first group underwent chemical skin treatment with 25% TCA while the other group was applied with 0.1% retinoic acid treatment. Following the 4 months’ treatment the patients were controlled three times in total for post lesional hypopigmentation, hyperpigmentation, scars, skin irritation and other possible changes per month. The pretreatment and first follow-up visit, and final control images were comparatively evaluated by three observers via specific software. Results : The healing rates of the group subject to retinoic acid were statistically higher (p < 0.05) compared to patients in the TCA group in the final follow-up visit following the treatment according to the first and second observers. On the other hand, according to the third observer, patients applied with retinoic acid presented with higher healing rates compared to those treated with TCA, however; this rate was not statistically significant (p > 0.05). The frequency of TCA- and retinoic acid-associated adverse effects was similar in both groups (p > 0.05). As a result of both treatments, a reduction in the quality of life scores as well as a pronounced recovery (p = 0.001) in the quality of life of those patients with skin aging was observed. Conclusions : The photo aging treatment option with 0.1% retinoic acid is cheaper and more feasible for patients compared to 25% TCA, and it is also as reliable and effective as TCA.